PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Wulansari, Retno; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTCorporate social responsibility is the form of corporate responsibility to improve social and environmentalproblems which has occurred by operational activities of the company whereas the implementation of goodcorporate governance basically has the objective to provide advances to the performance of a company to allparties who concerned with the company are underserved. The purpose of this research is (a) to examineempirically the corporate social responsibility disclosure give influence to firm value, (b) to examine empiricallythe implementation of good corporate governance give influence to the firm value. The data collection techniqueshas been performed by using documentation method in the form of annual financial statements of manufacturingcompanies which have been obtained from Indonesia Stock Exchange. The data analysis has been carried out byusing multiple linear regression analysis. Based on the results of the hypothesis test, it can be concluded that (1)corporate social responsibility disclosure give positive influence to the firm value. By conducting the practice ofcorporate social responsibility, it can enhance the company image in the eyes of the public and shareholders, (2)the implementation of good corporate governance give positive influence to the firm value, when the companyhas implemented the good corporate governance.Keywords: CSR, GCG, firm values.